A comparative study between excellent and average TESL students' perceptual learning styles / Nor Fazidah Jaafar - Jaafar, Nor Fazidah (Faculty of Education, 2014)
The study was conducted to compare learning styles of excellent and average (Teaching English as Second Language) TESL students. The purpose of this study was to identify the significant difference between preferential learning styles and students' academic achievement. To address research questions in the study, a survey was administered to 118 semester six and semester eight TESL students of Universiti Teknologi MARA (UiTM), Shah Alam. The subjects were later divided into two groups based on their CGPA. To analyze the data from the survey, descriptive analysis and T-test were used. Findings revealed that differences in learning style preferences existed within the excellent and average group of participants with excellent students least preferred Group learning style and average students least preferred Individual learning style. However, significant differences were not found between learning styles and academic achievement.